LIVE BED SHOW: The Paradox of Traumatic Memory in Autobiographical Performance - MacDonald, Kellie (Université d'Ottawa / University of Ottawa, 2022)
LIVE BED SHOW is an autoethnographic practice as research thesis exploring the apparent theoretical impossibility of reconciling the "unbridgeable gaps" of traumatic memory within autobiographical performance. Embracing an embodied poetics of failure, LIVE BED SHOW considers the possibility of employing the "ghosts" and "echoes" inherent to vinyl turntablism as a tool to represent traumatic memory in autobiographical performance. In doing so, it tests Karen Jürs-Munby's hypothesis that post-traumatic experience might share an affinity with the fragmented, non-linear, and repetitive structure of postdramatic performance.
Keywords: research creation; autoethnography; postdramatic; traumatic memory; autobiography; autobiographical performance; analogue sound; vinyl turntablism